Gas exchange and stomatal conductance of two wheat species at different soil water contents - Sassaki, Regina Miyuki; Machado, Eduardo Caruso (Pesquisa Agropecuaria Brasileira, 1999)
The objective of this work was to compare gas exchange rates and water status of two wheat species (Triticum aestivum L., "trigo normal", and Triticum durum L., "trigo duro") at different soil water contents. Plants were grown under greenhouse conditions in 0.13 m diameter, 0.30 m deep pots containing soil and during the period of grain development plants were submitted to water deficiency. So, CO2 assimilation rate, leaf water potential, stomatal conductance and transpiration rate were measured under controlled conditions (PPFD = 800 mmol m-2 s-1, T = 28oC). Water potential ranged from -0.3 to -2.4 and from -0.3 to -2.8 MPa, in "trigo normal" and "trigo duro", respectively. CO2 assimilation rate as a function of leaf water potential presented differences between the two species in terms of response pattern and tolerance to water deficit. In "trigo normal", CO2 assimilation rate was zero when water potential was around -2.4 MPa, while in "trigo duro" this was around 4 mmol m-2 s-1 when leaf water potential was around -2.8 MPa. Dry soil may potentially affect stomatal aperture.